Can spot urine measurement be a substitute for 24‐hour urine measurement to estimate sodium intake in adolescents? - Jie Dong; Xiaoyuan Zhao; Hongbo Dong; Yinkun Yan; Jie Mi (Wiley, 2021)
ABSTRACT Importance Several methods have been established in recent decades that allow use of spot urine to estimate dietary sodium intake. However, their accuracies have been controversial in children. Objective To validate the performance of three commonly used methods-the Kawasaki, Tanaka, and International Cooperative Study on Salt, Other Factors, and Blood Pressure (INTERSALT) methods. Additionally, this study explored the accuracies of the Tanaka and INTERSALT methods by using spot urine samples taken at four separate times. Method Forty‐one adolescents aged 14 to 16 years completed two non‐consecutive 24‐hour urine collections and their mean values were used as reference data. The second‐morning urine was used for assessment with the Kawasaki method; a casual spot urine and spot urine samples taken at four separate times (morning, afternoon, evening, and overnight) were used for assessment with the Tanaka and INTERSALT methods. Results The mean differences were 1801 mg, 542 mg, 47 mg, and −31 mg for the Kawasaki, Tanaka, INTERSALT1 (with potassium), and INTERSALT2 (without potassium) methods with their required spot urine, respectively. The proportions of relative difference levels within ± 10% were 4.9% for the Kawasaki method, 19.5% for the Tanaka method, 36.6% for the INTERSALT1 method, and 36.6% for the INTERSALT2 method. Interpretation The INTERSALT method seemed to provide minimally biased estimations of mean population sodium intake with casual spot urine. However, there is a need to be cautious regarding inconsistencies in estimation among different levels of sodium intake. The methods assessed in this study were unable to accurately estimate sodium intake at the individual level.